Hybrid governance structure between public company and private partners: the case of Infraero in the Brazilian airline sector - Paulo Burnier da Silveira (Revista Direito GV)
Abstract A public-private partnership (PPP) model has been adopted in Brazil for the modernization of its main national airports. Until 2017, the institutional setup imposed the public company Infraero to participate with 49% in the joint venture for the management of the airports subject to PPP. The remaining 51% shares belong to private companies, namely those that constitute the consortium group that won the correspondent public tender. This paper analyses this hybrid governance structure, including the main advantages and disadvantages, for both government and private parties, in maintaining a state-owned enterprise with a mandatory 49% share in the winner consortium. It focuses on five main aspects: access to knowledge; government influence on decisions, funding, and risk-sharing; cross subsidization and competition. The paper also summarizes its main findings and recommendations for future rounds of airport concessions in Brazil, in particular to underline overall inconveniences of the mandatory rule that imposes to Infraero a 49% share in all winner consortiums.